Targeting NF-kappaB-inducing kinase shapes B-cell homeostasis in myasthenia gravis - Xiaoyu Huang; Zhouao Zhang; Zhouyi Wang; Tiancheng Luo; Mingjin Yang; Xinyan Guo; Xue Du; Tianyu Ma; Yong Zhang (Journal of Neuroinflammation)
Abstract Background B cell immune dysregulation plays a critical role in myasthenia gravis (MG). However, targeted B-cell therapy such as rituximab may result in long-term peripheral B cell clearance and allow for the survival of plasma cells, contributing to frequent infections and relapses. Therefore, we aimed to identify potential novel therapeutic targets that preserve part of B cell function while inhibiting antibody-secreting cells (ASCs). Methods The transcriptome of sorted CD19+B cells obtained from MG patients in active and remission state was performed by RNA sequencing. The hallmark gene NF-kappaB-inducing kinase (NIK/MAP3K14) associated with NF-κB and TNF signaling was identified, and the expression levels of NIK in CD19+B cells, CD4+T cells and serum from new-onset MG patients and controls were validated by flow cytometry, qPCR and ELISA. In vitro and in vivo, the effects of NIK inhibitor (B022) on the function of CD19+B cells and CD4+T cells were detected under the MG PBMCs, sorted B cells and experimental autoimmune MG (EAMG) rat model, respectively. Results The expression levels of NIK were upregulated in CD19+B cells, CD4+T cells and serum from new-onset MG patients. Notably, increased serum NIK levels were positively correlated with disease severity and decreased with disease remission. NIK inhibitor B022 significantly reduced B-cell activation, proliferation, ASCs differentiation and pathogenic function, as well as CD4+T cell activation and Th17 cells differentiation in vitro. Intraperitoneal injection of B022 ameliorated the severity of EAMG rats, and reduced proportion of pathogenic B and T cell subsets, antibody levels and postsynaptic membrane damage. Conclusions Targeting NIK with small molecule kinase inhibitors can effectively shape B cell homeostasis, and exhibit protective effects in the EAMG rat model, which may be an effective novel treatment strategy for MG.